2014
DOI: 10.1371/journal.pone.0087575
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Multiple Types of Dehydrins in the Freezing Response in Loquat (Eriobotrya japonica)

Abstract: Dehydrins (DHNs) are a family of plant proteins typically induced in response to stress conditions that cause cellular dehydration, such as low temperatures, high salinity, and drought. Loquat (Eriobotrya japonica) is a perennial fruit crop that blossoms during winter. Loquat fruitlets are frequently injured by freezing. To evaluate the role of the EjDHNs in freezing resistance in loquat fruitlets, two cultivars of loquat, the freezing-sensitive ‘Ninghaibai’ (FS-NHB) and the freezing-tolerant ‘Jiajiao’ (FT-JJ)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 47 publications
3
22
0
Order By: Relevance
“…Five of these ten unigenes (Unigene 028024, Unigene 048324, Unigene 022315, Unigene 033567 and Unigene 022968) were annotated as DHN by NR from sequences of Malus × domestica , Corylus heterophylla and Phaseolus vulgaris . DHNs comprise one of the plant protein families typically induced by multiple stresses that cause cellular dehydration, and protect plant proteins and membranes from damage[ 68 , 69 ]. BjDHN2 and BjDHN3 exert a protective function on membranes under abiotic stresses, both of which are upregulated by low temperature, drought and salt stress in Brassica juncea [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Five of these ten unigenes (Unigene 028024, Unigene 048324, Unigene 022315, Unigene 033567 and Unigene 022968) were annotated as DHN by NR from sequences of Malus × domestica , Corylus heterophylla and Phaseolus vulgaris . DHNs comprise one of the plant protein families typically induced by multiple stresses that cause cellular dehydration, and protect plant proteins and membranes from damage[ 68 , 69 ]. BjDHN2 and BjDHN3 exert a protective function on membranes under abiotic stresses, both of which are upregulated by low temperature, drought and salt stress in Brassica juncea [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…With a decrease in temperature during dormancy, the amount of ROS increased, which can be seen in the increase of H 2 O 2 content in the present study ( Figure 5). Xu et al (2014) reported that H 2 O 2 content was high after cold temperature treatment in loquat fruitlets. SOD is the main enzyme responsible for scavenging ROS and for converting it into oxygen and H 2 O 2 (Cruzde-Carvalho, 2008), but in our results, increases in H 2 O 2 content were accompanied by decreases in SOD activity.…”
Section: Discussionmentioning
confidence: 99%
“…The peroxidase (POD, EC 1.11.1.7) activity was measured according to Chance and Maehly [68]. The activities of catalase (CAT, EC 1.11.1.6) and ascorbate peroxidase (APX, EC 1.11.1.11) were determined according to Xu et al [69]. The specific primers of C-repeat binding factors (CBFs) were designed according to Zhang et al [70].…”
Section: Analysis Of Physiological and Cbfs Expression Levelsmentioning
confidence: 99%